Toward Local Assessing urban disaster displacement risk. - Lloyd, Scott (My University, 2021)
Displacement risk associated with disasters and climate change is concentrated in cities and expected to increase in the coming years. Therefore, determining a hazard-prone city’s displacement risk profile is key to sustainable development, effective humanitarian response and long-term prevention of displacement. This report highlights why and how risk assessments need to become an integral part of urban planning, and presents an original tool that allows local authorities to assess disaster displacement risk in their urban area. The tool identifies drivers and triggers of displacement as well as vulnerable areas and urban populations at higher risk of displacement. It assesses data availability, urban governance, disaster risk management capacity and initiatives to mitigate displacement and ensure durable solutions for those affected. In addition, promising practices of urban planning strategies from around the world are high-lighted as examples which can be adapted to different risk profiles.
Keywords: Naturkatastrophe; Umweltschaden; Stadtzerstörung; Vulnerabilität; Risikoabschätzung; Obdachlosigkeit; Migration; Binnenwanderung; Stadtflucht; Displaced person; Klimaflüchtling